Effect of cellulose nanocrystals in a cellulosic liquid crystal behaviour under low shear (regime I): structure and molecular dynamics - Echeverria, Coro (2017)
We study the motion of a uniform thin rod released from rest, with the bottom end initially in contact with a horizontal surface. Our focus here is the motion of the bottom end as the rod falls. For small angles of release with respect to the horizontal, the rod falls without the bottom end slipping. For larger angles, the slipping direction depends on the static friction coefficient between the rod and the horizontal surface. Small friction coefficients cause the end to slip initially in one direction and then in the other, while for high coefficients, the end slips in one direction only. For intermediate values, depending on the angle of release, both situations can occur. We find the initial slipping direction to depend on a relation between the angle at which the rod slips, and a critical angle at which the frictional force vanishes. Comparison between experimental data and numerical simulations shows good agreement. (C) 2016 American Association of Physics Teachers.